Global Governments and Democratization - John B. Anderson (Washington University Journal of Law & Policy, 2001)
This essay addresses the questions of interpretation and reform that surround the United Nations and the UN Charter in consideration of a changing, global world. Particular attention is given to the need for "international civil society" to foster a culture of peace and justice. The paper poses a challenge for democratization and reform to mobilize and give voice to an empowered UN.
Keywords: Human rights; Civil society; Democracy; United Nations